2023
DOI: 10.1007/s10479-023-05241-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of analytics capability and sensing capability on operations performance: the moderating role of data-driven culture

Abstract: Studies indicate that organizational capability is a key factor in operational performance, and that both sensing and analytics capabilities have a significant influence on operational performance. This study develops a framework to examine the impact of organizational capability on operational performance, with a specific focus on the implementation of sensing and analytics capabilities. We combine strategic fit theory, the dynamic capability view, and the resource-based view to examine how micro, small, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…, 2021), supporting the notion that it is not enough to focus on technical aspects of data analytics (Chenger and Pettigrew, 2023). Our findings showed that DDC strengthened the impact of DAC on robustness but not resilience (RQ4), supporting the treatment of DDC as a moderator (Wong and Ngai, 2023). DDC implies that an organization exhibits a culture in which insights generated by data supersede intuition.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…, 2021), supporting the notion that it is not enough to focus on technical aspects of data analytics (Chenger and Pettigrew, 2023). Our findings showed that DDC strengthened the impact of DAC on robustness but not resilience (RQ4), supporting the treatment of DDC as a moderator (Wong and Ngai, 2023). DDC implies that an organization exhibits a culture in which insights generated by data supersede intuition.…”
Section: Discussionsupporting
confidence: 69%
“…DDC has been shown to be a necessary condition for organizations to take advantage of data analytics projects by making information processing more consistent and Developing resilient and robust supply chains facilitating the communication and dissemination of data insights across the organization (Karaboga et al, 2023). Previous research has treated DDC as either a moderator (Wong and Ngai, 2023) or a mediator (Karaboga et al, 2023) but without providing arguments in favor of one approach over the other. We follow Wong and Ngai (2023) and argue that DDC should be treated as a moderator as it strengthens the impact of DAC by ensuring congruence between technical and organizational aspects, leading to the following hypotheses:…”
Section: Data Driven Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Chatterjee et al (2021b) emphasized DCV and absorptive capacity theory and highlighted that data-driven organizations enhance their performance through optimal usage of data-based insights. Thus, it moderates the relationship between analytical capabilities, sensing capabilities, and operational performance (Wong & Ngai, 2023). This study has conceptualized marketing agility as a sensing capability; thus, the data-driven culture can also moderate the relationship between marketing agility and market performance.…”
Section: Data-driven Culture As a Moderatormentioning
confidence: 96%
“…The decisions taken by executives can be different, because the decisions depend on the assessment system and capabilities of each executive. (Haarhaus & Liening, 2020) concluded that three factors that influence DMC are managerial cognition, managerial social capital (Wong & Ngai, 2023), and managerial human capital (Eggers & Kaplan, 2009).…”
Section: Dynamic Managerial Capabilitiesmentioning
confidence: 99%